High-speed optical receivers with integrated photodiode in nanoscale CMOS - Tavernier, Filip; Steyaert, Michiel 1959- (Springer New York, 2011)
This book describes the design of optical receivers that use the most economical integration technology, while enabling performance that is typically only found in very expensive devices.  To achieve this, all necessary functionality, from light detection to digital output, is integrated on a single piece of silicon. All building blocks are thoroughly discussed, including photodiodes, transimpedance amplifiers, equalizers and post amplifiers. Provides a thorough explanation of all relevant aspects of receivers and optical receivers;   Describes all key building blocks of an optical receiver and their design trade-offs; Introduces new design solutions for every building block in order to improve its performance;  Illustrates all techniques and formulas with extensive examples and figures;  Includes several real, state-of-the-art chip implementations.